Anti-diabetic effect of metformin combined with peanut (Arachis hypogaea L.) on streptozotocin induced diabetic rats - Nazmin, Shehrina; Sultana, Nayma (Journal of Bangladesh Society of Physiologist, 2018)
Background: Diabetes mellitus (DM) is a common metabolic disorder. Metformin is the initial drug of choice for treatment of type 2 DM. In many cases, metformin mono-therapy cannot effectively achieve the targeted glycemic control. However, metformin along with peanut (Arachis hypogaea L.) may reduce blood glucose level more effectively. Objective: To evaluate the anti-diabetic effect of metformin in combination with peanut on streptozotocin induced diabetic rats. Methods: This experimental study was conducted in the Department of Physiology, Sir Salimullah Medical College, in 2016. Forty (40) Wistar Albino male rats, 90-120 days old, weighing 225-240 g (initial body weight) were taken and divided into four groups containing 10 rats in each group, i.e. Non-diabetic group (ND), Streptozotocin induced diabetic group (STZ), Diabetic group treated with metformin (STZ-M) and Diabetic group treated with metformin and peanut (STZ-MP). Diabetic model was developed by giving single intraperitoneal injection of streptozotocin (50mg/kg body weight) to STZ, STZ-M and STZ-MP groups on day-1. In addition, STZ-M group received metformin (500mg/kg body weight) orally and STZ-MP group received both metformin and peanut extract orally (both 500mg/kg body weight) once daily in the morning for 21 days (day-4 to day-24). After measuring the final body weight, rats were sacrificed on day-25. To observe glycemic status, Fasting Blood Glucose (FBG), serum insulin levels were estimated and HOMA-IR was calculated. Statistical analyses were done by one way ANOVA and Bonferroni test as applicable. Results: Mean FBG level and HOMA-IR were significantly (p<0.001) higher and serum insulin level and final body weight were significantly (p<0.001) lower in STZ group when compared to those of ND group. Whereas, FBG level and HOMA-IR were significantly (p<0.001) lower and insulin level and final body weight were significantly higher (p<0.001) in both STZ-M and STZ-MP groups in comparison to those of STZ group but more profound effects were found in STZ-MP group than those of STZ-M group. Conclusion: The present study revealed that, metformin combined with peanut was more effective to control glycemic status in diabetic rats than metformin alone. J Bangladesh Soc Physiol. 2018, December; 13(2): 59-67